CONSTRUCTION OF THE TENGKU AGUNG SULTANAH LATIFAH BRIDGE AND ITS IMPACT ON SIAK REGENCY (2001-2011): Pembangunan Jembatan Tengku Agung Sultanah Latifah dan Dampaknya Bagi Kabupaten Siak (2001-2011) - Bunari; Asyrul Fikri; rendi saputra bangun (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study investigates the historical context and multifaceted impact of the Tengku Agung Sultanah Latifah Bridge construction in Siak Regency, Riau, spanning the period from 2001 to 2011. Prior to its construction, the inhabitants of Siak Sri Indrapura City encountered significant challenges stemming from restricted access across the Siak River, a crucial national waterway and primary transportation artery. Dependence on pontoons, ferries, or traditional wooden canoes led to extensive queues, prolonged travel times, and inherent safety hazards, particularly for schoolchildren. These impediments severely hindered economic and social development, causing Siak to lag behind other districts and earning it the moniker of a 'ghost town. In response to these pressing issues, the inaugural Regent of Siak, Arwin AS, initiated the bridge project in 2002. The undertaking encountered considerable resistance, including opposition from the central government and legal disputes from shipping companies concerned about navigational disruptions. Nevertheless, through persistent efforts by the local government, the bridge was successfully completed and formally inaugurated in 2007 by President Susilo Bambang Yudhoyono. Currently, the Tengku Agung Sultanah Latifah Bridge functions not merely as critical infrastructure, enhancing transportation and stimulating economic activity, but also as a prominent tourist destination. This research specifically aims to delineate the community's challenges before the bridge's construction, detail the construction process, and analyze its profound impact on the developmental trajectory of Siak Regency.